Uji Aktivitas Antioksidan dan Penetapan Kadar Vitamin C Ekstrak Buah Naga Merah Keunguan (Hylocereus lemairei (Hook.) Britton & Rose) Secara Spektrofotometri UV-Vis - Zikra Azizah; Zulharmita Zulharmita; Eki Zulfian (Jurnal Farmasi Higea, 2017)
The research on antioxidant activity test and the determination of the degree of vitamin C from fruit extracts purplish red dragon (Hylocereus lemairei (Hook.) Britton & Rose) has been done. On this research fresh dragon fruit meat mashed with blender and maceration methode used ethanol solvent 96% with three repetitions. The results of maceration evaporated with rotary evaporator until viscous extract. The test of free radical DPPH deterrent and the determination the degree of vitamin C in extracts purplish red dragon fruit (Hylocereus lemairei (Hook.) Britton & Rose) using vitamin C as a comparison. On the antioxidant activity test, extract was made with various concentration i.e. 1000 µ g/mL, 1500 µ g/mL, 2000 µ g/mL, 2500 µ g/mL, 3000 µ g/mL, obtained the percentage of antioxidant activity was 28.57 %, 34.67 %, 41.81 % , 46.13 %, and 51.78 %. On the determination of the degree of vitamin C extract, the extract is made with concentration 1000 µ g/mL used spectrophotometer UV-Vis showed that the degree of vitamin C in extracts purplish red dragon fruit (Hylocereus lemairei (Hook.) Britton & Rose) was 24.79 mg/100 g dragon fruit.